UM ESTUDO DO USO DE VOCÁBULOS, EXPRESSÕES FIXAS E SEMIFIXAS MAIS FREQÜENTES EM CONTRATOS DE COMPRA E VENDA SUBMETIDOS À TRADUÇÃO JURAMENTADA - Camargo, Diva Cardoso de; Aubert, Francis Henrik (Intercâmbio, 2010)
Our paper intends to analyse similarities and differences in the use of more frequent words (types) as well as fixed and semi-fixed expressions found in purchase and sale agreements. Our study derives its theoretical sources from Baker’s (1992, 1996, 2004) proposal for Corpus-based Translation Studies, Berber Sardinha’s (2004) investigation on Corpus Linguistics, and Aubert’s (1998, 2003) essays on sworn translation.